Congenital Diaphragmatic Hernia Prenatal to Childhood Management and Outcomes - Molloy, Eleanor (IntechOpen, 2012)
Congenital Diaphragmatic hernia (CDH) occurs in approximately 1 in every 2,500 births and the cause is yet unknown. In CDH the diaphragm fails to form correctly, allowing herniation of the abdominal contents into the thoracic cavity and results in pulmonary hypolplasia. This book describes the embryology, genetics, antenatal diagnosis, management, associated congenital anomalies and long-term outcomes of children with CDH. It is a valuable up-to-date reference for pediatricians, neonatologists and allied health professionals who care for children with CDH.